Symptoms of menopause and health of women during perimenopause - Nagórska, Małgorzata; Sowa, Aneta; Wardak, Katarzyna; Lesińska-Sawicka, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Perimenopausal age is the time in a woman’s life, when her reproductive capacity declines. Characteristic symptoms in the majority of systems accompany this process. Aim. The aim of the study was to determine the symptoms of menopause and investigate the most common health problems in perimenopausal women. Materials and methods. The study involved 180 women in perimenopausal age (45-55 years). The subjects were mainly residents of rural areas (65%) and married (84%). Most of them declared secondary education (57%). A questionnaire developed by the authors was used in the study. Results. Most women observed typical menopausal symptoms mostly between 45 and 49 years of age. Most often, these were hot flushes, the second place was night sweats, and the third place was insomnia. Almost 40% of women are treated for chronic diseases, most of them for hypertension, thyroid disease and diabetes. Conclusions. The changes associated with perimenopausal age in the majority of respondents include genitourinary system, respiratory system, skeletal system and metabolic changes. Level of education influences the level of knowledge among women on the menopause. Women from rural areas used non-pharmacological methods to mitigate the symptoms of menopause to a greater extent.
Keywords: menopause; perimenopausal age; women; health